Diagnosis of optic nerve sheath meningioma during optic nerve sheath decompression. (2nd January 2017) - Meeker, Austin R.; Ko, Melissa W.; Carruth, Bryant P.; Strumpf, Kenneth B.; Bersani, Thomas A.
ABSTRACT: Optic nerve sheath meningioma (ONSM) is typically diagnosed based on clinical suspicion and imaging characteristics and is most often treated with radiation. Historically, biopsy, optic nerve sheath decompression, and debulking surgeries have been avoided for fear of optic nerve vascular disruption and tumor spread into the orbit. This is a case of a 48-year-old man who presented with unilateral optic disc edema, declining visual acuity, and a visual field defect. Despite an initial improvement with acetazolamide, his vision subsequently worsened. With an elevated lumbar puncture opening pressure and imaging showing right optic nerve sheath enhancement, the differential diagnosis included ONSM, perineuritis and idiopathic intracranial hypertension (IIH). Optic nerve sheath decompression (ONSD) with biopsy was performed, simultaneously decompressing the nerve and yielding a sample for pathologic analysis. A pathologic diagnosis of ONSM was made and treatment with radiation was subsequently initiated, but vision began to improve after the surgical decompression alone.